Remifentanil protects uterus against ischemia-reperfusion injury in rats - Atalay,Yunus Oktay (2015)
PURPOSE: To investigate the effects of remifentanil as an antioxidant and analyze the histopathologic, biochemical changes in experimental ischemia-reperfusion (I/R) exposed rat uteri. METHODS: Wistar albino rats were assigned to three groups (n = 7). 2h period of ischemia was followed by 1h of reperfusion in the I/R and the I/R-remifentanil groups. After ischemia, no drug was administered in the sham and I/R groups. In the I/R-remifentanil group, remifentanil infusion (2 μg/kg/min) was started in the ischemia period, and continued until the end of reperfusion. After the ischemic and reperfusion period, the ischemic uterine horns were removed surgically for biochemical and histopathologic examination. Tissue damage scores (endometrial epithelial glandular leukocytosis, degeneration, and endometrial stromal changes) were examined. Malondialdehyde levels and catalase, superoxide dismutase enzyme activities in tissue were measured. RESULTS: We found significantly lower epithelial leukocytosis and cell degeneration in the I/R-remifentanil group (p<0.05). Remifentanil administration significantly decreased concentrations of malondialdehyde, and increased catalase and superoxide dismutase enzyme activities (p<0.05). CONCLUSION: Remifentanil appears to protect the uterine tissue against ischemia-reperfusion and can be used safely in uterus transplantation.